An Analysis of Teacher Professional Development Policy Provision in Nepal - Basnet, Mahendra (Journal of TESON, 2026)
This article analyzes the Teacher Professional Development (TPD) policy provisions in Nepal, drawing on the data obtained from the policy review and interviews with teachers from three community schools in Nepal. Particularly, this article focuses on the policy text, teachers’ understanding, and local practices. This is more concerned with how TPD affects teachers’ professional life. For this, I adopted the qualitative research design to explore subjective experiences of selected teachers. I used an unstructured interview conducted with selected school teachers. Along with the TPD policy document, I also analysed the policy provision on teacher training. The findings indicate that the TPD framework focuses on competency-based training package in two phases to teachers, and teachers have positive responses to the training as it is motivating to them.  However, the driving factor for them to be motivated is the promotion in profession, rather than learning for professional competencies. Although the TPD policy provision is conceptually sound, it couldn’t achieve the expected outcomes due to ineffective implementation.